2019
DOI: 10.18203/2349-2902.isj20191921
|View full text |Cite
|
Sign up to set email alerts
|

Review of currently used standardized measures of quality of life after ventral incisional hernia repair: systematic review

Abstract: After advancements in surgical and anaesthetics expertise and increased life spans among patients with complex abdominal surgeries, clinicians are left with the next main challenge, to how to improve the quality of life in patients with incisional hernia resulted from previous complex abdominal surgeries. To date there is no consensus over the choice of instrument and time frame for its administration in the literature. The aim of this review was to search for the current literature on measurement of quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Besides, all patients with Rives-Stoppa hernia repair had the same mesh features which avoid the influence of different mesh features on patient pain, sensation, and quality of life. Fourth, although it was shown in the literature reviews that complete assessment of the quality of life after hernia surgery is best achieved using a general scale with a specific scale and a validated pain scale [ 28 ], we did not use a specific pain score. We assessed pain using items in the SF-36 questionnaire, EuraHS QoL questionnaire, and CCS.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, all patients with Rives-Stoppa hernia repair had the same mesh features which avoid the influence of different mesh features on patient pain, sensation, and quality of life. Fourth, although it was shown in the literature reviews that complete assessment of the quality of life after hernia surgery is best achieved using a general scale with a specific scale and a validated pain scale [ 28 ], we did not use a specific pain score. We assessed pain using items in the SF-36 questionnaire, EuraHS QoL questionnaire, and CCS.…”
Section: Discussionmentioning
confidence: 99%
“…Please note that the AAS is only included here under the umbrella of CAWH specific tools since it has been outlined as such in a systematic review Grove et al [ 15 ] and by Majeed et al [ 46 ]. Although it is possible that the authors of these systematic reviews looked at the origins of the tools identified via their search strategies this is not addressed within their papers.…”
Section: Discussionmentioning
confidence: 99%